Effect of a Simple Information Booklet on Pain Persistence after an Acute Episode of Low Back Pain: A Non-Randomized Trial in a Primary Care Setting - Coudeyre, Emmanuel (Public Library of Science, 2007)
OBJECTIVE: Mass-media campaigns have been known to modify the outcome of low back pain (LBP). We assessed the impact on outcome of standardized written information on LBP given to patients with acute LBP. METHODS: Design: A 3-month pragmatic, multicenter controlled trial with geographic stratification. Setting: Primary care practice in France. Participants: 2752 patients with acute LBP. Intervention: An advice book on LBP (the “back book”). Main outcome measures: The main outcome measure was persistence of LBP three months after baseline evaluation. RESULTS: 2337 (85%) patients were assessed at follow-up and 12.4% of participants reported persistent LBP. The absolute risk reduction of reporting persistent back pain in the intervention group was 3.6% lower than in the control group (10.5% vs. 14.1%; 95% confidence interval [−6.3% ; −1.0%]; p value adjusted for cluster effect = 0.01). Patients in the intervention group were more satisfied than those in the control group with the information they received about physical activities, when to consult their physician, and how to prevent a new episode of LBP. However, the number of patients who had taken sick leave was similar, as was the mean sick-leave duration, in both arms, and, among patients with persistent pain at follow-up, the intervention and control groups did not differ in disability or fear-avoidance beliefs. CONCLUSIONS: The level of improvement of an information booklet is modest, but the cost and complexity of the intervention is minimal. Therefore, the implications and generalizability of this intervention are substantial. TRIAL REGISTRATION: ClinicalTrials.gov NCT00343057